When does brand matter more than our senses?: The influence of touching or smelling experience on product evaluation - Garcia-Marques,Teresa (2020)
In this work we examine the interaction between brand and direct experience on product evaluation. Specifically, we selected two products (perfume and paper) whose intrinsic quality can be inferred directly through sensory experience (i.e., scent and writing experience, respectively). Results from one field and one laboratorial experiment showed that brand impacts the perception of a product, overriding the information offered by direct sensory experience with the product. Importantly, this was more likely to occur in processing conditions that induce low elaboration (e.g., low motivation). We further discuss how these results contribute to understand the effect as supported by having brand as a heuristic or promoting a belief that is able to bias our perceptions.